Analysis of the Influence of Inflation on Economic Growth in Indonesia: Panel Data Regression Approach - Yakub, Andryirawan; Fitrianti, Retno; Sopian, Andi; Sapanang, A. Baso Aditya; Fitrianti, A. Nur; Hamka, Hamka (Darul Yasin Al Sys, 2024)
Inflation and economic growth are two macroeconomic phenomena that are interrelated and have significant implications for the stability and economic welfare of a country. Inflation, which is measured as the general increase in the price of goods and services over time, can affect various aspects of the economy, including people's purchasing power, investment levels, and consumption decisions. This study uses a quantitative approach with a panel data regression method to analyze the influence of inflation on economic growth in Indonesia using the Eviews 12 application. The results of this study indicate that the influence of inflation on economic growth is not strong enough to be considered statistically significant in the period analyzed. Although there was a small positive effect of inflation on economic growth, these results showed that inflation was not the main factor affecting economic growth in Indonesia during the period. Therefore, policymakers must consider other factors that may have a more significant influence in formulating effective economic strategies.